Multi-input DC-AC Inverter for Hybrid Renewable Energy Power System - Mohd Azman Rosli; Nor Zaihar Yahaya; Zuhairi Baharudin (International Journal of Electrical and Computer Engineering (IJECE), 2016)
The objective of this paper is to design a multi-input dc-ac inverter integrated photovoltaic array, wind turbine and fuel cell in order to simplify the hybrid power system and reduce the cost.  The output power characteristics of the photovoltaic array, wind turbine and fuel cell are introduced. The operational principle and technical details of the proposed multi-input dc-ac inverter is then explained. The proposed inverter consists of a three input flyback dc-dc converter and a single phase full bridge dc-ac inverter. The control strategy for the proposed inverter to distribute the power reasonably to the sources and it achieved a priority of the new energy utilization is discussed. This multi-input dc-ac inverter is capable of being operated in five conditions and power delivered to the ac load can be either individually or simultaneously. First to third condition occurs when the power delivered from either renewable energy sources individually, fourth condition happens when power is demanded from two sources simultaneously, and finally when power are available from three sources simultaneously. The proposed inverter has been simulated by employing NI Multisim 12.0 circuit simulator.